Increasing Student Motivation and Learning Outcomes Through the Application of the Cooperative Script Model in Archives Learning - Haeriwati, Haeriwati (Universitas Negeri Makassar, 2022)
The cooperative script model is a simple method that can be used to practice a skill or procedure with a study partner. The main objective of this research is to increase motivation and learning outcomes in Archives class X OTKP 4 SMK Negeri 2 Palu for the 2021/2022 academic year. The learning outcomes in question are specifically in the cognitive/knowledge domain. This research is a class action research. The research subjects were 18 class X OTKP 4 students consisting of 7 boys and 11 girls. While the research procedure consists of 4 stages, namely: planning, implementation, observation and reflection. Furthermore, data analysis was carried out through three stages, namely data reduction, data presentation, and data/conclusion verification. The application of the Cooperative Script model can increase student motivation and learning outcomes in Archives class X OTKP 4 SMK Negeri 2 Palu for the 2021/2022 academic year.